EXPERIMENTAL AND NUMERICAL STUDY OF CONTROLLED FLUTTER TESTING IN A LINEAR TURBINE BLADE CASCADE - Václav Sláma; Bartoloměj Rudas; Petr Eret; Volodymyr Tsymbalyuk; Jiří Ira; Aleš Macalka; Lorenzo Pinelli; Federico Vanti; Andrea Arnone; Antonio Alfio Lo Balbo (Acta Polytechnica CTU Proceedings)
In this paper, experimental testing of flutter and numerical simulations using a commercial code ANSYS CFX and an in-house code TRAF are performed on an oscillating linear cascade of turbine blades installed in a subsonic test rig. Bending and torsional motions of the blades are investigated in a travelling wave mode approach. In each numerical approach, a rig geometry model with a different level of complexity is used. Good agreement between the numerical simulations and experiments is achieved using both approaches and benefits and drawbacks of each technique are commented in this paper. It is demonstrated that both used computational techniques are adequate to predict turbine blade flutter. It is concluded that validated numerical tools can provide a better insight of flutter phenomena of operationally flexible steam turbine last stage blades.